THE EFFECT OF USING INTERNAL CONTROL UNDER THE ELECTRONIC OPERATING SYSTEM - Dr. Azadeh Barati; Waseem Saleh Khalaf; Oday Fathi Jarullah; Sulaiman Hamad Atiyah; Sarmad Hussein Atiyah (Scholar Express Journals, 2022)
Due to the increasing in technological development, the importance of using the computer in the interior has increased because of its advantages that help in raising the efficiency of that system, and the importance of researching the importance of internal work, and, and, and, and, and, and, and the effectiveness of the internal management system, reducing errors, identifying errors and the framework Before it happens, as is the importance of research in knowing the methods, procedures and changes that occur to the internal management in the idea of operating an electronic environment. It performs the function of building control, an organization that works on building engineering, a building engineering organization, building engineering, building engineering, building engineering, building engineering, building engineering, building and building engineering, buildings, and sometimes, And sometimes many ways. She has motives like humans that push him to cheat and steal. And the best areas that permeate that system with its advantages in building a good and effective system to reduce the operating environment in the electronic operating environment. The environment is highly experienced in computer software to deal with the risks and viruses exposed to it.
Keywords: internal key; advantages of electronic operation; electronic